Carrying Tremendous Weight : Trauma Theory Applied to Horror Fiction in Carrie by Stephen King and The Silence of the Lambs by Thomas Harris - Lindroos, Roosa (My University, 2021)
This thesis studies the relationship between real-life trauma and horror literature. The main focal point is how the experiences of female characters in horror stories reflect the trauma people face in real life. Throughout the research I use literary trauma theory and psychoanalytic criticism as the main theories for analysis. These theories are utilized in studying the primary sources Carrie by Stephen King and The Silence of the Lambs by Thomas Harris. The aim is to consider the similarities between the traumatizing themes involving the women depicted in these books and the real-life events that have a significant part in causing trauma. Through my study of how trauma is received and experienced in fictious depictions of it, I conclude that such depictions are closely tied to real-life anxieties that are especially felt by women. Whether the trauma is physical, sexual or emotional, oftentimes the consequences are dire and can have transgenerational effects. Trauma is a common element in horror literature, and the characters chosen for analysis depict different aspects of it, as well as different ways to write about trauma. Additionally, the research concludes that trauma experienced by women is often afflicted by a patriarchal society which seeks control over women. This is present in the novels’ trauma narratives accordingly, as characters are faced with issues of motherhood and sexuality, both topics that have historically caused discord in real-life issues and the literary world.
Keywords: Stephen King, Carrie, Thomas Harris, Silence of the Lambs, literary trauma theory, trauma transfer, horror fiction, patriarchal terrorism